2015
DOI: 10.1002/pssc.201510039
|View full text |Cite
|
Sign up to set email alerts
|

PEALD AlN: Controlling growth and film crystallinity

Abstract: We report on the growth kinetics and material properties of aluminium nitride (AlN) films deposited on Si(111), with plasma enhanced atomic layer deposition (PEALD). Tri‐methyl aluminium (TMA) and NH3‐plasma were used as the precursors. The ALD window was identified in terms of the process parameters, and it showed that a 0.1 s of TMA pulse, 8 s of NH3‐plasma pulse, and 350 °C were the optimal conditions for ALD to occur. In‐situ spectroscopic ellipsometry (SE), using a Cauchy optical model, was used to monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Both the Al 2p and N 1s peaks were slightly asymmetric, indicating the presence of different bonding features associated with nitrogen in the AlN thin films. [28,41,42]. As shown in Figure 5a, mainly Al-N bonds and ignorable Al-O bonds were observed.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Both the Al 2p and N 1s peaks were slightly asymmetric, indicating the presence of different bonding features associated with nitrogen in the AlN thin films. [28,41,42]. As shown in Figure 5a, mainly Al-N bonds and ignorable Al-O bonds were observed.…”
Section: Resultsmentioning
confidence: 83%
“…Our observation confirmed that co-adsorption of TMA and N 2 H 4 was self-limiting by forming a monolayer at substrate temperature <350 • C, while above this temperature reaction was rapid and formed a thick film of AIN. Consequently, the CVD effect became significant and an increase of GPC could be observed [16,17] as deposition temperature is up to 350 • C. It is also worth noting that the ALD window of AlN using TMA is narrow in earlier studies [27,28]. Furthermore, the growth rate of thermal ALD-AlN films from TMA and NH 3 was inconsistent in previous reports.…”
Section: Resultsmentioning
confidence: 87%
“…In the literature, higher crystalline quality of the PE-ALD grown AlN was observed on Si (111), and it was mainly attributed to the hexagonal structure of Si (111) substrate. 27 The lattice parameter c was determined using the (002) reflection of hexagonal phase from diffraction patterns of GaN grown on different substrates. First interplanar spacing values (d hkl ) were calculated using Bragg's law and these values were then substituted in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the effect of different substrates on material properties of PA-ALD grown AlN thin films has been investigated, where they demonstrate that Si (111) is a better substrate for AlN growth. 27 In this work, we have studied and compared the properties of GaN thin films grown on Si (100), Si (111), and c-plane sapphire substrates by using hollow-cathode plasma-assisted ALD (HCPA-ALD) at 200 C.…”
Section: Introductionmentioning
confidence: 99%
“…ALD has been previously used to grow III-nitride thin films where the impact of various growth parameters on film quality has been investigated in detail. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] In this work, we demonstrate the precision fabrication of long-range ordered vertical GaN, AlN, and InN hollow nanocylindrical arrays on Si substrates using AAO membrane templated hollow-cathode plasma-assisted atomic layer deposition (HCPA-ALD). Uniform and vertically oriented nanocylinder arrays confirm the ability to precisely tune III-nitride nanostructure geometry via AAO-templated PA-ALD in comparison with other commonly used high-temperature growth techniques, which mainly allow one to obtain elongated nanostructures without three-dimensional precision thickness control.…”
Section: Introductionmentioning
confidence: 99%